A Regularized Multi-Task Learning Approach for Cell Type Detection in Single-Cell RNA Sequencing Data - Upadhyay, Piu; Ray, Sumanta (Frontiers in Genetics, 2022)
Cell type prediction is one of the most challenging goals in single cell RNA-sequencing (scRNA-seq) data}. Existing methods use unsupervised learning to identify signature genes in each cluster, followed by a literature survey to lookup those genes for assigning cell types. However, finding potential marker genes in each cluster is cumbersome which impedes the systematic analysis of single cell RNA sequencing data. To address this challenge, we proposed a framework based on regularized multi-task learning (RMTL) that enables us to simultaneously learn the subpopulation associated with a particular cell type. Learning the structure of subpopulations is treated as a separate task in the multi-task learner. Regularization is used to modulate the multi task model (say $W_1,W_2, … W_t$) jointly according to the specific prior. For validating our model, we train it with reference data constructed from single cell RNA-seq experiment and apply it to a query dataset. We always predict completely independent data (the query dataset) from the reference data which is used for training. We have checked the efficacy of the proposed method by comparing it with other state-of-the-art techniques well known for cell type detection. Results reveal that the proposed method performs accurately for detecting cell type in scRNA-seq data, thus can be utilized as a useful tool in the scRNA-seq pipeline.